Exploration of elastomeric and polymeric liquid crystals with photothermal actuation: A review. (December 2019) - Rastogi, Prasansha; Njuguna, James; Kandasubramanian, Balasubramanian
Graphical abstract: Highlights: Discussion of liquid crystals undergoing photothermal response. Outline on agents as heat-engendering source in electromagnetic radiation. Prospect of photothermal actuation in liquid crystals with 4D Printing. Exploration of liquid crystals in biomedical treatment. Abstract: Recent research in soft materials is an exhilarating category which has been transcending boundaries for variety of functional applications. This category also stems liquid crystals whose stimuli-responsive feature has fantasized researchers for application arrays in actuators and biomedical. Liquid crystals evince dual characteristics of liquid and solids empowering them to reversibly transit on external actuation. The after-effect of irradiating photons on liquid crystals (LC) facilitate outlying functioning and are engineered with gold nanorods, dyes, graphene and carbon nanotubes among others which greets to incoming stimulus and participates in transference of light energy to perceivable transformation through heat drive. This is progressively explored in medical domain for drug delivery, tissue engineering, cancer treatment, and other disciplines of medicine and bio-mimicking. Additionally, photothermal trigger equips localized punctilious treatment outshining diffusion assisted heating and enables spot treatment. However, LC utilization is burgeoning towards 3D printing, characterizing it as 4D Printing. Present review framework probes LC and its photothermal actuation chemistry in the medical domain. Furthermore, it reflects on LC potential in smart manufacturing in 3D/4D printing, its challenges (limited concentration of filler, its miscibility, and actuation cycle fatigue) and future likelihood.